Direct synthesis and characterization of endohedral zinc(II) hemicryptophane complex. (28th September 2022) - Makita, Yoshimasa; Akagi, Yuya; Aoyagi, Yuka; Yakabe, Genta; Hirai, Yuya; Nomoto, Akihiro; Fujiwara, Shin-ichi; Ogawa, Akiya
Graphical abstract: Highlights: CTG-based tripodal ligand which had triethylene glycol spacers and quinolinols was synthesized. An endohedral Zn(II) hemicryptophane complex was directly synthesized from the CTG-based tripodal ligand. The Zn(II) hemicryptophane complex encapsulated choline within the cavity. Abstract: Endohedral metal hemicryptophanes are attractive metal complexes with secondary coordination sphere models. Here, an endohedral Zn(II) hemicryptophane complex is directly synthesized using a triethylene glycol chain as a moderate length spacer between the cyclotriguaiacylene (CTG) and quinolinol units of the novel tripodal ligand. The guest of choline was encapsulated within the cavity of Zn(II) hemicryptophane complex.